Inflammatory bowel disease and risk of gastric, small bowel and colorectal cancer: a meta-analysis of 26 observational studies - Wan, Qianyi; Zhao, Rui; Xia, Lin; Wu, Yutao; Zhou, Yong; Wang, Yong; Cui, Yaping; Shen, Xiaoding; Wu, Xiao-Ting (Journal of cancer research and clinical oncology, 2021)
Purpose The purpose of this meta-analysis was to assess the associations between inflammatory bowel disease (IBD) and risk of the gastric, small bowel and colorectal cancer. Methods We searched the PubMed and Web of Science for observational studies published before June 2020, and the quality of each included study was evaluated according to the Newcastle–Ottawa–Scale. Results Twenty-six studies comprising 531 449 IBD patients and more than 65 million reference individuals were included. Although IBD was significantly associated with 67% increased risk of the total gastric, small bowel and colorectal cancer. After stratifying by cancer location, IBD mainly increased the risk of intestinal cancer instead of gastric cancer. Furthermore, Crohn’s disease (CD) significantly increased the risk of both small bowel cancer and colorectal cancer, while ulcerative colitis (UC) only increased the risk of colorectal cancer. In subgroup analysis, associations between IBD and risk of total gastric, small bowel and colorectal cancer were similar between male and female, except for that male IBD patients but not female had a significantly higher risk of small bowel cancer. Additionally, IBD patients in different geographical areas had different associations with risk of various gastrointestinal tract cancers. Conclusions IBD is mainly associated with increased risk of cancers in the lower gastrointestinal tract, including small bowel cancer and colorectal cancer. Because studies about the association between IBD and risk of gastric cancer and the populations in Asia are limited, more observational studies are required in the future.